2014
DOI: 10.1080/1331677x.2014.952113
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneity analysis of south-eastern European countries according to tourism competitiveness performances

Abstract: The purpose of this research is to analyse the competitiveness of south-eastern Europe (SEE) countries with the help of The Travel and Tourism Competitiveness Index (TTCI) and The Global Competitiveness Index (GCI), as well as to explore the correlation and mutual influence of these two indices. The aim is to explore the homogeneity of SEE countries according to tourism competitiveness performance. The research was conducted on the basis of secondary data sources and statistical methods, with emphasis on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Studies using the Global Competitiveness Index (GCI) data as well as TTCI data in the measurement of destination competitiveness are also included in the literature. For example, Jovanović et al (2014) evaluated the competitiveness of South-eastern European countries using TTCI and GCI data and showed that there is a high correlation between TTCI and GCI data and South-eastern European countries that examined in the study are not homogeneous in competition based on the data of these indices. They also provided a premise framework for comparing the tourism performances of different countries and setting goals and strategies for increasing tourism competitiveness.…”
Section: Determination Of Destination Competitiveness Of the Selected Mediterranean Destinations By Entropy Based Edas Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using the Global Competitiveness Index (GCI) data as well as TTCI data in the measurement of destination competitiveness are also included in the literature. For example, Jovanović et al (2014) evaluated the competitiveness of South-eastern European countries using TTCI and GCI data and showed that there is a high correlation between TTCI and GCI data and South-eastern European countries that examined in the study are not homogeneous in competition based on the data of these indices. They also provided a premise framework for comparing the tourism performances of different countries and setting goals and strategies for increasing tourism competitiveness.…”
Section: Determination Of Destination Competitiveness Of the Selected Mediterranean Destinations By Entropy Based Edas Methodsmentioning
confidence: 99%
“…Reviewing the literature on destination competitiveness, there are studies related to using different models to measure competitiveness (Crouch & Ritchie, 1999;Gooroochurn & Sugiyarto, 2005;Heath, 2003;World Economic Forum [WEF], 2019); determining the strengths and weaknesses of the destinations by using the scores of the 14 subindexes comprising the Travel & Tourism Competitiveness Index (TTCI) as criteria (Hassan & Uşaklı, 2013); examining the competitiveness of a single country (Göral, 2017;Tomić & Stoiljković, 2015); a holistic examination of the destinations depending on the subindexes and pillars (Bălan et al, 2009); using TTCI data with another index (Jovanović et al, 2014). In addition to these studies, there is a study in which competitiveness of 141 countries are analyzed by entropy method depending on the subindexes in TTCI (Göral, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Webster and Ivanov (2014) attempt to explore this idea in depth, using the Travel and Tourism Competitiveness Index (TTCI) as a variable to identify country competitiveness; they conclude that there is no positive relationship between a destination's competitiveness and its contribution to economic growth. On the other hand, Jovanović et al (2014) use the Global Competitiveness Index (GCI) in addition to the TTCI, and by means of a cluster analysis, they analyse the competitiveness of southeastern European countries, showing a high correlation between both indices. The study results advise these regions on the need to innovate their strategies for tourism development, with the goal of increasing their global competitiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of south-eastern European countries provides the initial framework for benchmarking the tourism performance of different countries, and determination of objectives and strategies for improving tourism competitiveness [48]. The quality aspect leads to the success of tourism development is any destination [26]. It is one of the sustainable tourism development [22].…”
Section: Introductionmentioning
confidence: 99%